2011
DOI: 10.1001/jama.2011.749
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Time to Initiation of Adjuvant Chemotherapy and Survival in Colorectal Cancer

Abstract: In a meta-analysis of the available literature on time to AC, longer time to AC was associated with worse survival among patients with resected colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
398
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(421 citation statements)
references
References 31 publications
9
398
2
12
Order By: Relevance
“…In einer retrospektiven Analyse von Kohortenstudien [868]. wurde eine inverse Korrelation zwischen dem Zeitpunkt des Beginns einer adjuvanten Chemotherapie und dem Überleben berechnet.…”
Section: Hintergrundunclassified
“…In einer retrospektiven Analyse von Kohortenstudien [868]. wurde eine inverse Korrelation zwischen dem Zeitpunkt des Beginns einer adjuvanten Chemotherapie und dem Überleben berechnet.…”
Section: Hintergrundunclassified
“…This turnaround time has been recommended in other guidelines for molecular tumor testing. 105,126,127 Ideally, the transitional time between test ordering, tissue block selection, block retrieval, and shipment to the performing laboratory should be included in the 10-day timeframe. Consequently, laboratories should make every effort to minimize delays in securing appropriate tissue blocks for testing.…”
Section: Postanalytical Variablesmentioning
confidence: 99%
“…The timing of adjuvant chemotherapy may also have a considerable effect on survival outcomes and has been largely overlooked in the present studies. Several metaanalyses showed that the longer the chemotherapy is delayed the shorter survival is in patients with colorectal cancer [50,51] . One of the reasons why colon cancer responds to adjuvant chemotherapy and rectal does not may be prompt administration of adjuvant chemotherapy [9] .…”
Section: Potential Pitfalls Of the Current Evidencementioning
confidence: 99%